Wind-induced response control model for high-rise buildings based on resizing method - Choi, Se Woon; Seo, Ji Hyun; Lee, Hong Min; Kim, Yousok; Park, Hyo Seon (Journal of Civil Engineering and Management, 2015)
A variety of methods have been applied to reduce the effect of the wind-induced vibration of a high-rise building as the excessive wind-induced vibration at the top of a high-rise building can cause physical and psychological discomfort to the user or the residents. For structural engineers, the most effective approach to control the wind-induced responses of high-rise buildings would be to control the stiffness or natural frequency of the building. This paper presents a practical design model to control the wind-induced responses of a high-rise building. In the model, the stiffness of a high-rise building is maximized to increase the natural frequency of the building by the resizing algorithm. The proposed design model is applied to control the wind-induced vibration of an actual 37-storey building during the initial stage of its structural design.